The clinical and virological features of two children's coinfections with human adenovirus type 7 and human coronavirus-229E virus - Liu, Shelan; Zhu, An; Pan, Jinren; Ying, Lihong; Sun, Wanwan; Wu, Hanting; Zhu, Haiying; Lou, Haiyan; Wang, Lan; Qin, Shuwen; Yu, Zhao; Cai, Jian; et al. (Frontiers in Public Health, 2022)
Objective Human adenovirus (HAdV) coinfection with other respiratory viruses is common, but adenovirus infection combined with human coronavirus-229E (HCoV-229E) is very rare. Study design and setting Clinical manifestations, laboratory examinations, and disease severity were compared between three groups: one coinfected with HAdV-Ad7 and HCoV-229E, one infected only with adenovirus (mono-adenovirus), and one infected only with HCoV-229E (mono-HCoV-229E). Results From July to August 2019, there were 24 hospitalized children: two were coinfected with HAdV-Ad7 and HCoV-229E, and 21 were infected with a single adenovirus infection. Finally, one 14-year-old boy presented with a high fever, but tested negative for HAdV-Ad7 and HCoV-229E. Additionally, three adult asymptotic cases with HCoV-229E were screened. No significant difference in age was found in the coinfection and mono-adenovirus groups (11 vs. 8 years, p = 0.332). Both groups had the same incubation period (2.5 vs. 3 days, p = 0.8302), fever duration (2.5 vs. 2.9 days, p = 0.5062), and length of hospital stay (7 vs. 6.76 days, p = 0.640). No obvious differences were found in viral loads between the coinfection and mono-adenovirus groups (25.4 vs. 23.7, p = 0.570), or in the coinfection and mono-HCoV-229E groups (32.9 vs. 30.06, p = 0.067). All cases recovered and were discharged from the hospital. Conclusion HAdV-Ad7 and HCoV-229E coinfection in healthy children may not increase the clinical severity or prolong the clinical course. The specific interaction mechanism between the viruses requires further study.